The swordsman's oath : the second tale of Einarinn - McKenna, Juliet E. (New York : EOS, 2000)
"Ryshad was a warrior, a sworn man pledged to defend the Empire and his lord with his sword and his life. Livak was a thief, a woman as dangerous and cunning as she was beautiful. Brought together by fate--and the wily wizard Shiv--these unlikely allies once traveled to the frozen lands of the North to find answers to an ancient mystery. Instead, though, they discovered death and worse at the hands of the Elietimm, a band of evil sorcerers who nearly destroyed them."--Cover.
Keywords: Oaths -- Fiction; Wizards -- Fiction; Fantasy fiction